Differential effects of structurally different lysophosphatidylethanolamine species on proliferation and differentiation in pre-osteoblast MC3T3-E1 cells - Fumiaki Makiyama; Shiori Kawase; Aoi William Omi; Yusuke Tanikawa; Taishi Kotani; Teruki Shirayama; Naoyuki Nishimura; Taiga Kurihara; Naoto Saito; Jun Takahashi; Takeshi Uemura (Scientific Reports)
Abstract Lysophosphatidylethanolamine (LPE) is a bioactive lipid mediator involved in diverse cellular functions. In this study, we investigated the effects of three LPE species, 1-palmitoyl LPE (16:0 LPE), 1-stearoyl LPE (18:0 LPE), and 1-oleoyl LPE (18:1 LPE) on pre-osteoblast MC3T3-E1 cells. All LPE species stimulated cell proliferation and activated the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) 1/2. MAPK/ERK1/2 activation by 16:0 LPE and 18:1 LPE was inhibited by the Gq/11 inhibitor YM-254890, while activation by 18:0 LPE was blocked by the Gi/o inhibitor pertussis toxin. Intracellular Ca2+ transients were triggered by 16:0 LPE and 18:1 LPE but not by 18:0 LPE, with YM-254890 suppressing these responses. These results suggest that 16:0 and 18:1 LPE act via Gq/11-coupled G protein coupled receptors (GPCRs), and 18:0 LPE acts via Gi/o-coupled GPCRs. Furthermore, receptor desensitization experiments suggested that each LPE acts through distinct GPCRs. Interestingly, 18:0 LPE suppressed osteogenic differentiation, reducing mineralization, alkaline phosphatase activity, and osteogenic gene expression, whereas 16:0 LPE and 18:1 LPE had no such effects. These results suggest the physiological significance of LPEs in bone formation and indicate that different LPE species and their receptors play distinctive roles in this process.